Strategi Public Relations melalui Acara Sitcom OK-JEK di NET TV - Kusuma, Gamaliel Gumilar; Darmastuti, Rini (Faculty of Communications Science, Dr. Soetomo University, 2019)
By using a constructivist approach, this descriptive qualitative study seeks to explore how the Public Relations Strategy as an education is present through the sitcom television series, OK-JEK. Data obtained through in-depth interviews and content analysis of 20 episodes of OK-JEK sitcom shows. The results of this study are: first, Sitcom OK-JEK presents educational messages that are full of meaning. Educational points such as safety riding/ driving safety, performance, service, complaints, facilities, and the use of applications are the values of education contained in OK-JEK shows. Second, the Public Relations strategy, both in terms of promotion, image enhancement and so on, develops from rigid and changing cognitive things using a more creative and communicative approach. Third, the messages delivered through each episode of OK-JEK, build community understanding of online motorcycle taxi services. Situation Comedy OK-JEK presents shows that contain educational messages, which unwittingly build an understanding of the public about the presence of new transportation modes in their midst.